Temperature preference and distribution of juvenile Arctic grayling (Thymallus arcticus) in the Williston watershed, British Columbia Canada. - Hawkshaw, Sarah C. F. (Author); Shrimpton, Mark (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2011)
The habitat requirements of juvenile Arctic grayling (Thymallus arcticus) were assessed in the Williston watershed, British Columbia, where the population is currently red-listed (critically imperiled). Temperature preferences of juvenile Arctic grayling was assessed behaviorally using a shuttlebox system, and an information theoretic approach analysis of logistic regression models was used to evaluate the influence of environmental factors on the distribution of juvenile Arctic grayling throughout the Williston watershed. Temperature preference of juvenile Arctic grayling did not vary between the two tributaries in the watershed (p = 0.77) and the average preferred temperature was 16.84 ± 0.66 °C (n = 28). Comparisons of the preferred temperature to ambient water temperatures suggested that juvenile Arctic grayling will avoid areas where maximum water temperature is above the preferred temperature. There was a positive association between juvenile Arctic grayling occurrence and stream order (SO) and stream order multiplied by distance from the Williston reservoir (SDRxSO), as well as a negative association with the mean daily water temperature variance (varT) and average water temperature (aveT). Overall these findings suggest that large river systems are important juvenile Arctic grayling habitat and management decision should be made to ensure protection of this habitat throughout the range of this species. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1741116